Salivary glands adenoid cystic carcinoma: a molecular profile update and potential implications - da Silva, Fernanda Jardim; Carvalho de Azevedo, Juscelino; Ralph, Ana Carolina Lima; Pinheiro, João de Jesus Viana; Freitas, Vanessa Morais; Calcagno, Danielle Queiroz (Frontiers in Oncology, 2023)
Adenoid cystic carcinoma (ACC) is an aggressive tumor with a high propensity for distant metastasis and perineural invasion. This tumor is more commonly found in regions of the head and neck, mainly the salivary glands. In general, the main modality of treatment for ACC is surgical resection, and in some cases, postoperative radiotherapy is indicated to assist in the local control of the disease. However, no effective systemic treatment is available for patients with advanced disease. Furthermore, this tumor type is characterized by recurrent molecular alterations, especially rearrangements involving the MYB gene family, C-KIT overexpression, and alterations in the NOTCH signaling pathway. The impact of these alterations on the clinical management of ACC patients is still unclear. In this review, we report the genetic and cytogenetic findings on head and neck ACC, highlighting possible targets for therapeutic interventions.